Pengaruh Belanja Pemerintah Daerah Bidang Pendidikan dan Kesehatan terhadap Indeks Pembangunan Manusia di Kabupaten Timor Tengah Selatan - Sandi G. Muskanan; Thobias E. D. Tomasowa (JAKA - Jurnal Jurusan Akuntasi, 2019)
This study aims is to examine the effect of local government spending on education and health to the Human Development Index (HDI) at Timor Tengah Selatan regency, both partially and simultaneously. The variables which used in this study are Regional Government Spending in Education (X1), Regional Government Spending in Health (X2) and Human Development Index (Y). The data used in this paper are quantitative from secondary sources, namely The Central Statistics Office and The Regional Financial and Asset Management Office, Timor Tengah Selatan regency. Data analysis using linear regression analysis using t test (partial) to test the hypotheses 1 and 2 and F test (simultaneous) to test the hypothesis 3. The T test results for the hypotheses 1 and 2 show significance values of 0,000 and 0.006, which means H1 and H2 are accepted. The F test results to test hypothesis 3 show a significance value of 0,000, which means H3 is accepted. The conclusion of the process that can be drawn is that government spending in the education and health sectors both partially and simultaneously has a positive effect to the Human Development Index at Timor Tengah Selatan Regency.